2004
DOI: 10.1080/10408690490464276
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer-Based Antimicrobial Packaging: A Review

Abstract: The term antimicrobialpackaging encompasses any packaging technique(s) used to control microbial growth in a food product. These include packaging materials and edible films and coatings that contain antimicrobial agents and also techniques that modify the atmosphere within the package. In recent years, antimicrobial packaging has attracted much attention from the food industry because of the increase in consumer demand for minimally processed, preservative-free products. Reflecting this demand, the preservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
337
0
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 632 publications
(348 citation statements)
references
References 133 publications
1
337
0
10
Order By: Relevance
“…The antimicrobial and antifungal effects of ginger essential oil were found to be high in some studies (Alzoreky & Nakahara, 2003;Bonjar et al, 2004;Chao et al, 2000;Martins et al, 2001;Sharma & Sharma, 2011;Shetty, 1997;Stoyanova et al, 2006;Wei & Shibamoto, 2010) but weak or absent in others (Onyeagba Ugbogu, Okeke & Iroakasi, 2004;Wannissorn et al, 2005;Zaika, 1988). Additionally, the antimicrobial effect of ginger was found to vary depending on certain factors, such as plant species, harvesting time, geographical conditions and the ratio of active ingredient (Cagri et al, 2002;Cha & Chinnan, 2004;Joerger, 2007;Sağdıç, Kuşçu, Özcan, & Özçelik 2002;Torlak & Nizamoglu, 2011). In our study, it was found that the addition of 1.5% (v/v) of ginger essential oil to WPI+S+Alg-based coating had a bacteriostatic effect on E. coli O157:H7 and a bactericidal effect on S. aureus during 30 days of storage.…”
Section: Microorganisms Daymentioning
confidence: 99%
“…The antimicrobial and antifungal effects of ginger essential oil were found to be high in some studies (Alzoreky & Nakahara, 2003;Bonjar et al, 2004;Chao et al, 2000;Martins et al, 2001;Sharma & Sharma, 2011;Shetty, 1997;Stoyanova et al, 2006;Wei & Shibamoto, 2010) but weak or absent in others (Onyeagba Ugbogu, Okeke & Iroakasi, 2004;Wannissorn et al, 2005;Zaika, 1988). Additionally, the antimicrobial effect of ginger was found to vary depending on certain factors, such as plant species, harvesting time, geographical conditions and the ratio of active ingredient (Cagri et al, 2002;Cha & Chinnan, 2004;Joerger, 2007;Sağdıç, Kuşçu, Özcan, & Özçelik 2002;Torlak & Nizamoglu, 2011). In our study, it was found that the addition of 1.5% (v/v) of ginger essential oil to WPI+S+Alg-based coating had a bacteriostatic effect on E. coli O157:H7 and a bactericidal effect on S. aureus during 30 days of storage.…”
Section: Microorganisms Daymentioning
confidence: 99%
“…Active packaging technology is a relatively novel concept beneficial for extending the product shelf-life, maintaining its nutritional and sensory quality, as well as contributing to the microbial safety [2]. The ability of edible film or coating as a type of active packaging to carry some products additives such as antioxidants, antimicrobials, colorants, flavors, fortified nutrients and spices are being studied [3].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the moisture content will become less [31]. It is shown by the moisture content of shrimp shells which is about 60-65% [32]. Chitinolytic Activity of T. harzianum Molds Chitinolytic activity of molds is defined as the ability of molds to degrade chitin into other simpler compounds, e.g.…”
Section: Study Of Glukosamine Production From Shrimp Shells (Hardoko mentioning
confidence: 99%